Meningkatkan Penguasaan Simple Present Tense Dan Adjective Melalui Karangan Deskriptif Siswa - Nurdin Nurdin; Ismi Adinda; Al Khansa Nova Misbahillah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Writing is one of the activities in learning English that tests students' abilities, especially in mastering Tenses and vocabulary. This PkM aims to improve students' understanding and mastery, especially in using the Simple Present Tense and Adjectives through the activity of writing a simple essay. The type of text chosen as the research media is descriptive text. This is because the Simple Present Tense and Adjective are mostly used in writing the text. This PKM activity was carried out at Sasmita Jaya Vocational School 2 for three days, from 12 to 14 April 2023. The method used in this research is quantitative, referring to the theory by Heidi Dulay Taksonomi, namely Surface Strategy Taxonomy. From the research results, it was found that descriptive text media proved successful in increasing students' mastery of Simple Present Tense and Adjective.